Balance and quality of life after total knee arthroplasty - Daniel Araujo Fernandes (Revista Brasileira de Ortopedia)
ABSTRACT Objective: To evaluate the change in balance and quality of life in patients undergoing total knee arthroplasty for primary gonarthrosis. Method: Patients aged 60 years or older were evaluated in relation to the balance and quality of life before total knee arthroplasty and six months after surgery. To assess balance, this study used the Motor Scale Test for the Elderly; quality of life was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index questionnaire and the Short Form Health Survey. A control group consisting of healthy adults, age- and gender-paired, was used to compare the balance after surgery results. Results: Twenty-eight patients completed the study, of a total of 37 arthroplasties. The mean age was 70.18 ± 6.17 years. All variables were statistically significant (p ≤ 0.05) for improved balance and quality of life after arthroplasty. It was observed that, after knee arthroplasty, the level of balance does not reach that expected for healthy individuals (p ≤ 0.05). Conclusion: Total knee arthroplasty is effective at improving balance six months after surgery, as well as all domains of quality of life. However, it is not able to restore balance to a level comparable to that of healthy individuals.